Knowledge Level towards Breast Cancer and Breast Self-Examination among Medical Students of Indonesia - Andri Rezano; Hesti Lina Wiraswati; Savira Ekawardhani; Melia Juwita Adha; Nurul Mufliha Patahuddin; Veronica Oladitha Siagian; Siti Silvia Nur Shofa Shamantri; Erlangga Ing Geni Bisma Pratama; Liana Awalia Lutfunnisa; Asep Wiryasa; Hansen Wangsa Herman; Marhendra Satria Utama (Global Medical & Health Communication (GMHC), 2022)
Breast cancer is a life-threatening disease among Indonesian women. The etiology of breast cancer is still uncertain, and therefore adequate primary prevention is difficult. Early diagnosis improves cancer prognosis while also reducing medical costs, substantially reducing mortality rates. Knowledge and awareness of breast cancer risk factors and their screening may help women take preventive measures. The community service program aimed to assess the level of understanding of undergraduate medical students on breast cancer and breast self-examination (BSE). It was a one-group pretest-postest quasi-experimental study to measure the level of knowledge of 100 medical students in Indonesia from August 20th, 2020, to February 27th, 2021. The participants were asked 36 questions, which was an adaptation of previous questionnaires. A mini-lecture managed the program that focuses on risk factors and early detection. Furthermore, pretest and post-test were conducted to analyze the knowledge level before and after the dissemination. The participants included in this study were mostly 20 years and above (62%). The average recognition of breast cancer and its early detection was not high. The knowledge of breast cancer among medical students was found to be moderate. The efficacy of dissemination among medical students was apparent in knowledge change. However, good cancer awareness, especially breast cancer, needs to be established and integrated through effective cancer educational programs in the medical curricula. Hence, modification of the medical curriculum through extensive training on breast cancer preventive measures and early diagnosis is required.